PERAN DISIPLIN KERJA DALAM MEMEDIASI PENGARUH KERJASAMA TIM DAN STRES KERJA TERHADAP KINERJA PEGAWAI - Yaqin , Muhammad Ainul; Violinda , Qristin; Kurniawan, Bayu (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
This study aims to examine and analyze: (1)the effect of teamwork on employee performance at BPKPAD Demak, (2)the effect of work stress on employee performance at BPKPAD Demak, (3)the effect of teamwork on work discipline at BPKPAD Demak, (4)the effect of work stress on work discipline at BPKPAD Demak, (5)the effect of work discipline on employee performance at BPKPAD Demak, (6)the effect of teamwork on employee performance through work discipline at BPKPAD Demak, (7)the effect of work stress on employee performance through discipline work at BPKPAD Demak. This research is a causal associative research and uses quantitative methods with a descriptive approach. Sampling used a saturated sample with a total of 75 respondents from BPKPAD Demak Regency employees. The data analysis method uses structural equation modeling (SEM) with an alternative partial least square (PLS). The results showed that: (1)teamwork has a positive and significant effect on employee performance, (2)work stress has a positive and significant effect on employee performance, (3)teamwork has a positive and significant effect on work discipline, (4)work stress has an effect positive and significant effect on work discipline, (5)work discipline has a positive and significant effect on employee performance, (6)teamwork has a positive and significant effect on employee performance through work discipline, (7)teamwork has a positive and significant effect on employee performance through discipline work.